Analisis Puisi “Tiada” Karya Joko Pinurbo Menggunakan Pendekatan Struktural - Putri, Ayu Setiyo; Rahayu, Putri Shogita; Munaris, Munaris; Prasetyo, Heru (Universitas Lampung, 2024)
Poetry is a type of literary art that uses the elegance of language to convey emotions, ideas and experiences. Understanding the message buried in the poet's words makes poetry analysis important. In this article, examines poetry “Tiada” by Joko Pinurbo with a structural approach to uncover the deep meaning hidden in the form of poetry. The structural approach in analyzing poetry focuses on the structure of the poem which includes form, rhyme, rhythm, tone, and repetition. This study uses a qualitative descriptive methodology. The approach used is a structural approach. Data collection techniques using documentation studies. Puisi adalah jenis seni sastra yang menggunakan keanggunan bahasa untuk menyampaikan emosi, gagasan, dan pengalaman. Memahami pesan yang terkubur dalam kata-kata penyair membuat analisis puisi menjadi penting. Dalam artikel ini, mengkaji puisi “Tiada” karya Joko Pinurbo dengan pendekatan struktural untuk mengungkap makna mendalam yang tersembunyi dalam bentuk puisi. Pendekatan struktural dalam menganalisis puisi berfokus pada struktur puisi yang meliputi bentuk, rima, irama, nada, dan pengulangan. Penelitian ini menggunakan metodologi deskriptif kualitatif. Pendekatan yang digunakan adalah pendekatan struktural. Teknik pengumpulan data menggunakan studi dokumentasi.Keywords: poetry, structure of poetry, structural approach